Food Quality Certificates and Research on Effect of Food Quality Certificates to Determinate Ignored Level of Buying Behavioral: A Case Study in Hitit University Feas Business Department - CAGIRAN KENDIRLI, Hulya; ULUSOY, Gürkan (Journal of Economic Development, Environment and People, 2014)
Nowadays, food and food industry has become one of the most important sectors for manufacturers and consumers. Many countries of the world including Turkey have been developed and implemented many standards for food safety and presentation of food to ensure safe consumption. In this study, we studied on the most common of these standards through HACCP and ISO 22000 standards. The purpose of this study is, to determine students' awareness and ignores of level of food quality and food quality certification during their food shopping. This research has conducted with survey in the Hittite University, Faculty of Economics and Administrative Sciences, Business Administration by 256 students are attending to this department. Department student number is 775 in totally. We have determined some hypotheses in the context of research and we applied cluster analysis, chi-square analysis and correlation analysis to the research. According to results of a significant relationship was found between hypotheses. We considered 260 students. After calculating with 0,95 confidence interval and 0,05 tolerance we have to reach 258 students. We used the Cronbach’s Alfa for testing the reliability of survey. Cronbach’s Alfa is settled between 0 and 1 and for reliability of scale and it must be over 0,60 for acceptance to survey. Our survey’s scale has been 0,79 and we can said that, it is a reliable scale for this survey study. According to result of research, there is no relationship between demographic specialties of students and ignored of food and quality legislation. But there is relationship between sexuality and ignored of food and quality legislation.